(3GdMb aj GdEaUGM h GdTaGajI h GdeYQaI aj fXGe MhceI GdTQcGJ GdSYhOj (B/ s - (3gGOj Hf Ydj eMeO GdjGejs; (3SejMI eUWai GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3LGA HGdaUd GdChd GdMOjK Yf eaghe hfTCI MhceI GdTQcGJ hfWGbgG, hPcQfG Cf MhceI GdTQcGJ EWGQ bGfhfj hEOGQj jMce GOGA GdTQcI jJMbb ef NdGdg GdeMGaXI Ydj Mbhb GdeSGgejf hGdeYGedI GdYGOdI dge hGdMaGX Ydi eUGdM Phh GdTCf (B. (3haj GdaUd GdKGfj JfGhdfG eHOC GdEaUGM hGdTaGajI, hHjfG JYQja GdEaUGM hGdTaGajI hbdfG CfgeG jbJVjG EXgGQ GdeYdheGJ hGdcTa YfgG ddZjQ, hChVMfG GdYdGbI Hjf GdEaUGM hGdTaGajI, hbdfG Cf GdEaUGM LRA ef GdTaGajI, hGdEaUGM GdcGed jDOj Edj GdTaGajI haj GdaUd GdKGdK JfGhdfG GdENdGd HeHOC GdEaUGM hGdTaGajI, hajg HjfG GdeYdheGJ GdOGNdjI GdJj jYO GdEOdGA HgG eMd GdENdGd HGdEaUGM hGdTaGajI, hJJejR GdeYdheGJ GdOGNdjI HNUGFU KdGK HCf Jchf eMOOI hSQjI heDKQI Ydj CSYGQ GdChQGb GdeGdjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2016(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B141-153s
Keywords: (3fXGe MhceI GdTQcGJ GdSYhOjs; (3GdGaUGM hGdTaGajIs; (3fWGb MhceI GdTQcGJs; (3CgejI MhceI GdTQcGJs; (3eMd GdGaUGMs; (3eQGbH GdMSGHGJs; (3GdTQcI GdeUOQI ddChQGb GdeGdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs